2008
DOI: 10.1099/vir.0.2008/000133-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of sheep with visna/maedi virus via the conjunctival space

Abstract: Experiments were performed to determine whether visna/maedi virus (VMV), a small ruminant lentivirus (SRLV), could infect sheep via ocular tissues. The EV1 strain of VMV was administered into the conjunctival space of uninfected sheep, and the animals monitored for the presence of provirus DNA and anti-VMV antibodies in blood. The results showed that provirus DNA appeared in peripheral blood mononuclear cells of all animals within a few weeks of receiving either 10 6 TCID 50 or 10 3 TCID 50 of VMV. Of the anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…In addition, the flock should also be tested for MVV, and seronegative and seropositive sheep should be isolated from each other. Aerosol transmission through respiratory tract and experimentally via ocular tissue is another route of viral transmission (Peterhans et al 2004;McNeilly et al 2007;Niesalla et al 2008). Complete eradication of the infection will be possible when detailed information on the genetic characteristics (in many geographical regions) of infected flocks and individual animals become available.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the flock should also be tested for MVV, and seronegative and seropositive sheep should be isolated from each other. Aerosol transmission through respiratory tract and experimentally via ocular tissue is another route of viral transmission (Peterhans et al 2004;McNeilly et al 2007;Niesalla et al 2008). Complete eradication of the infection will be possible when detailed information on the genetic characteristics (in many geographical regions) of infected flocks and individual animals become available.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of the latter to infection shows a gradation with nasal transmission being the least efficient followed by the trachea then the lower lung [97,99]. Recently, infection via conjuctival tissues has been demonstrated experimentally with an efficiency estimated to be intermediate between tracheal and lower lung infection [100]. This suggests that respiratory aerosols generated by coughing may transmit infection via a conjunctival route.…”
Section: Transmissionmentioning
confidence: 97%
“…Viral DNA and antigen were detected in affected eyelids. Recently, it was shown that infection and inflammatory disease in conjunctival tissue can be induced experimentally in sheep [100]. No equivalent conjunctivitis has been described in HIV infections to date, despite the presence of virus in tears and conjunctival cells [103].…”
Section: Other Organsmentioning
confidence: 99%
“…15 Successful experimental infections with SRLVs have been performed using viral strains isolated from natural field infections 25,48 using different inoculation routes such as intravenous, intratracheal, intracerebral, intra-articular, or conjunctival. 25,32,40 However, more studies are needed to evaluate tissue/organ tropism upon experimental infection with SRLVs to enhance our understanding of the pathogenesis of the different clinical forms. The main objective of this work was to study comparatively the tissue tropism and the associated pathology of two autochthonous SRLV field strains of different tissue origin using an experimental infection in sheep via the bone marrow route and to determine if SRLV lesions could be produced in this experimental model.…”
mentioning
confidence: 99%